Cardiopulmonary exercise testing in athletes: Expect the unexpected - Petek, B. J.; Gustus, S. K.; Wasfy, M. M. (Current Treatment Options in Cardiovascular Medicine, 2021)
Purpose of review: Cardiopulmonary exercise testing (CPET) is a tool designed to assess the integrated function of the cardiac, pulmonary, vascular, and musculoskeletal systems to produce an exercise effort. CPET may be performed for performance purposes as part of optimizing a training program or for clinical purposes in athletes with established cardiovascular disease or in those with symptoms suggestive of cardiopulmonary pathology. Most normative values used for CPET parameters have been derived in the general population, in whom there will be expected differences in exercise physiology as compared to a trained athlete. In this review, our goal is to examine current available data on expected findings on CPET in athletes, highlight how these differ from the general population-derived normative values, and identify areas in need of further research to optimize the application of CPET in athletes. Recent findings: Athletes demonstrate differences in exercise hemodynamic and gas exchange profiles as compared to non-athletes including higher cardiac output, faster heart rate recovery, higher peak V?O2, higher prevalence of exercise-induced arterial hypoxemia, and lower breathing reserve. Summary: CPET is an important tool to optimize performance and assess for underlying pathology in an athletic population. The impact of routine, vigorous physical activity on exercise physiology should be integrated into determination of what constitutes a normal CPET result in an athletic individual.